Preparation of PEGylated cationic nanoliposome-siRNA complexes for cancer therapy. (31st October 2018) - Haghiralsadat, Fateme; Amoabediny, Ghasem; Naderinezhad, Samira; Forouzanfar, Tymour; Helder, Marco N.; Zandieh-Doulabi, Behrouz
Abstract: Cationic liposomes have been investigated as non-viral vectors for gene delivery for more than a decade to overcome challenges associated with viral gene delivery. However, due to instability of liposomes, siRNA delivery is still a serious problem. In this study, we developed stealth PEGylated liposome formulations and focused on the effects of PEGylated liposomes on parameters related to size, zeta potential, polydispersity index, siRNA-loading efficiency and long-term stability of the siRNA-liposome complex. We were able to generate siRNA lipoplexes that could be very efficiently loaded, did not aggregate, could be stored at 4 °C for at least 6 months with only marginal release (1–5%) of siRNA and enhanced intracellular delivery of siRNA. Moreover, we could demonstrate that PEGylation positively contributed to all these parameters compared to liposomes, which were not PEGylated. The prepared lipoplex was successfully silenced J1P1 expression in MG-63 osteosarcoma cell line. In conclusion, our novel PEGylated liposomes have high potential for systemic delivery of siRNA and can improve in vivo stability of free siRNA and also siRNA lipoplexes. Graphical Abstract: UF0001